An oxidation-resistant, high-temperature-resistant high-entropy alloy light-transmitting electromagnetic shielding mesh and a preparation method thereof
Patent Information
- Application Number
- CN202611408463.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-13
AI Technical Summary
这是因为纯金属原子自扩散系数高,晶粒易粗化,导致网栅尖端、边缘发生塑性变形甚至断裂;同时,纯金属与蓝宝石等硬质衬底的热膨胀系数严重失配(差值>10 ppm/K),热冲击下极易分层剥离
步骤S1的清洗预处理确保衬底表面洁净,提高后续膜层附着力;
Smart Images

Figure CN122909834A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic shielding optical materials technology, and in particular, to an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid and its preparation method. Background Technology
[0002] With the rapid development of electronic information processing technology and radio frequency applications, the electromagnetic environment faced by optical windows in electronic information systems, optoelectronic detection equipment, and radio frequency link front-ends is becoming increasingly complex. Particularly in applications such as aerospace cockpit observation windows, optoelectronic detection equipment, and radio frequency front-end optical windows, the demand for window materials that combine high light transmittance and strong electromagnetic shielding is particularly urgent. These windows must not only ensure high transmittance in specific light bands (such as visible light or infrared) to meet observation requirements, but also exhibit superior electromagnetic shielding effectiveness (typically >50dB) under long-term or pulsed irradiation under high-power, high-frequency electromagnetic waves (MHz-GHz band) to protect downstream precision electronic equipment. This places far more stringent requirements on the high-temperature thermal stability and oxidation resistance of the receiving end's transparent electromagnetic shielding materials than in conventional applications.
[0003] Existing technologies mainly employ aperture-type grids made of pure metals (Au, Cu, Ag, Cr, etc.). However, under high-power microwave irradiation, this type of grid exhibits the following drawbacks: First, high-temperature thermal-structural failure. The skin effect causes current to concentrate on the grid surface, and Joule heating raises the local temperature to 300-500℃. This is because pure metal atoms have a high self-diffusion coefficient, and the grains are prone to coarsening, leading to plastic deformation or even fracture at the grid tips and edges. At the same time, the thermal expansion coefficients of pure metals and hard substrates such as sapphire are severely mismatched (difference > 10 ppm / K), making them extremely prone to delamination under thermal shock. Simply increasing the linewidth would sacrifice light transmittance, while introducing a buffer layer would increase complexity and fail to eliminate the concentration of thermal stress at the nanoscale.
[0004] Second, high-temperature oxidation failure. The oxidation rate of pure metals increases exponentially at high temperatures, resulting in porous oxides (such as Cu2O) that cannot prevent oxygen from diffusing inwards, leading to a sharp increase in resistance and a decrease in shielding effectiveness. While existing technologies can temporarily block oxygen by coating the mesh surface with anti-oxidation coatings (such as graphene or ITO), the interface between the coating and the metal substrate will also fail under high-power microwave irradiation due to thermal mismatch and atomic interdiffusion. Furthermore, the coating itself increases the number of processing steps and may affect light transmittance.
[0005] Third, high-frequency shielding effectiveness is insufficient. Most pure metallic materials are diamagnetic or paramagnetic, with a relative permeability μr≈1. They rely solely on conductivity to reflect the electric field component, lacking absorption of the magnetic field component. At high frequencies, the skin effect leads to attenuation of reflection effectiveness, and strong eddy current losses exacerbate the Joule heating effect. While existing technologies can improve shielding effectiveness to some extent by optimizing grid geometry (such as reducing the period and increasing the linewidth), this comes at the cost of reduced light transmittance. Although transparent conductive oxides such as ITO can suppress eddy currents, the conductivity of these materials is far lower than that of metals, resulting in insufficient shielding effectiveness under the same geometric parameters. Furthermore, they are brittle and difficult to fabricate into micron-sized grids.
[0006] Therefore, developing a novel mesh material that simultaneously satisfies the requirements of high light transmittance, high shielding, high temperature resistance, and oxidation resistance is a bottleneck that existing technologies struggle to overcome. This invention is a solution proposed based on this technical problem. Summary of the Invention
[0007] One of the objectives of this invention is to provide an anti-oxidation, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh.
[0008] To achieve the above-mentioned objectives, the specific technical solution is as follows: An antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid includes a transparent substrate and a grid array disposed on the transparent substrate; The grid array is composed of a high-entropy alloy thin film, the high-entropy alloy comprising Fe, Co, Ni, Cr, and B, with a Cr content of 14-25 at.% and a B content of 0.05-0.2 at.%. The high-entropy alloy film has columnar crystal morphology inside, and the average width of the grains is 10-20 nm.
[0009] According to embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects: This invention presents an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid. Through multi-principal-element alloy design and synergy with micro / nano structures, it significantly improves high-temperature thermal stability and electromagnetic shielding effectiveness while ensuring high light transmittance. The components include Fe, Co, Ni, and Cr. Utilizing the hysteresis diffusion effect and lattice distortion effect of the high-entropy alloy, it effectively suppresses long-range atomic migration at high temperatures, preventing grain coarsening and grain boundary slip, thereby maintaining the microstructural integrity of the grid lines. Meanwhile, the introduction of ferromagnetic elements such as Fe, Co, and Ni endows the alloy with excellent soft magnetic properties, enabling it to produce hysteresis loss and natural resonance absorption of the magnetic field component of high-frequency alternating electromagnetic fields, converting electromagnetic wave energy into heat energy dissipation, thus making up for the inadequacy of pure metals relying solely on conductivity to reflect the electric field component.
[0010] Element B (content of 0.05-0.2 at.%) segregates at grain boundaries to form borides, which pins grain boundary slip, significantly improves grain boundary bonding, inhibits intergranular cracking at high temperatures, and ensures the structural integrity and thermal creep resistance of submicron grid lines under severe thermal shock.
[0011] A Cr content of 14-25 at.% ensures the formation of a sufficiently continuous and dense oxide passivation film at high temperatures. If the Cr content is below 14 at.%, a continuous passivation layer cannot be formed (as shown in Comparative Example 1), while if it is above 25 at.%, it may lead to increased alloy brittleness. Within this ratio range, the elements achieve an optimal balance of sheet resistance, high-temperature stability, oxidation resistance, and soft magnetic properties of the grid through multi-principal synergistic effects.
[0012] The high-entropy alloy thin film exhibits a columnar crystal morphology, which offers several unique advantages: First, the columnar crystals grow along the film thickness direction, forming numerous longitudinal grain boundaries along the grid linewidth direction. These grain boundaries strongly scatter electron transport, significantly increasing the film's resistivity. This effectively suppresses eddy current losses under high-frequency alternating electromagnetic fields, reduces Joule heating, alleviates local temperature rise and thermal stress in the grid, and enhances long-term service stability. Second, the nanoscale grains (10-20 nm) provide high-density nuclei for subsequent use in high-temperature environments. Utilizing the hysteresis diffusion effect of the high-entropy alloy, grain growth is suppressed during high-temperature service, and the grain size remains at the nanometer or submicron level (even after heating at 1000℃ for 16 h, the grain size is approximately 300 nm, still far smaller than micrometer-level coarsening). Third, the columnar crystal boundaries serve as ideal sites for boron element segregation, facilitating the uniform distribution of grain boundary borides, enhancing grain boundary pinning, and further improving high-temperature creep resistance. The nano-columnar crystal structure and the composition design of the high-entropy alloy work synergistically to build the long-term structural stability of the grid under extreme high temperature and high power electromagnetic wave environments.
[0013] In summary, Fe, Co, and Ni provide soft magnetic shielding, Cr provides anti-oxidation passivation, and B provides grain boundary strengthening. The synergy of these three elements enables the mesh to achieve a combination of high light transmittance (>85%), high shielding (>50dB), resistance to high-temperature grain coarsening, resistance to delamination, and resistance to oxidation under high-power, high-frequency electromagnetic wavelength time irradiation (reaching a high temperature of 1000℃). This solves the technical problems of existing pure metal meshes being prone to thermal deformation, oxidation, and shielding effectiveness degradation under high-frequency and high-power conditions.
[0014] According to one embodiment of the present invention, the high-entropy alloy further comprises at least one of Al, Ti, V, Nb, Mo, W, Ta, Zr, and Mn. Preferably, the high-entropy alloy comprises Al and Ti. Al has high oxygen-binding activity and preferentially diffuses and oxidizes to the grid surface in a high-temperature, oxygen-rich environment, forming a dense, continuous, and thermodynamically stable passivation film. This effectively blocks further penetration of oxygen atoms into the film, protecting the internal conductive cores such as Ni, Co, and Fe from oxidation, thereby maintaining long-term electromagnetic shielding effectiveness. Elements with large atomic radii or high melting points, such as Ti, V, Nb, Mo, W, and Ta, can significantly enhance the hysteresis diffusion effect of the high-entropy alloy, preventing plastic deformation or fracture of the grid under thermal stress.
[0015] At least one element selected from Al, Ti, V, Nb, Mo, W, Ta, Zr, and Mn works synergistically with Fe, Co, Ni, and Cr to maintain the grain size of the grid at the nanometer level (around 300 nm, significantly better than traditional materials) after working in a high-temperature vacuum environment of 1000℃ for 16 hours. Furthermore, a self-healing anti-oxidation layer is formed on the surface, solving the technical problems of easy oxidation and thermal deformation of pure metal grids.
[0016] Preferably, the passivation film formed by Al, the hysteresis diffusion effect brought by Ti, and the grain boundary pinning and anti-grain boundary sliding effect brought by B have a synergistic effect. One forms a passivation film on the surface, one acts on grain boundary pinning, and one acts on grain deceleration, thereby constructing a three-dimensional high-temperature structural stability defense line.
[0017] According to one embodiment of the present invention, in the high-entropy alloy, the Ni content is 30-55 at.%, the Co content is 12-26 at.%, the Cr content is 14-25 at.%, and the Fe content is 8-20 at.%. The Ni content of 30-55 at.% imparts excellent face-centered cubic phase stability and corrosion resistance to the alloy; the 12-26 at.% Co and 8-20 at.% Fe, in synergy with Ni, induce excellent soft magnetic properties in the solid solution, such as high permeability and low coercivity. This is the core source of high-frequency hysteresis loss and natural resonance absorption, and enhanced electromagnetic wave absorption capability.
[0018] According to one embodiment of the present invention, the high-entropy alloy comprises Al and Ti, wherein the content of Al is <8.0 at.% and the content of Ti is <8.0 at.%. The above proportions ensure the formation of an oxide passivation film and solid solution strengthening while avoiding excessive addition that could lead to an excessive decrease in the alloy's conductivity or processing difficulties.
[0019] According to one embodiment of the present invention, the high-entropy alloy contains 5.83-6.01 at.% Al and 3.95-4.08 at.% Ti.
[0020] According to one embodiment of the present invention, the content of element B in the high-entropy alloy is ≤0.1 at.%.
[0021] According to one embodiment of the present invention, the composition of the high-entropy alloy, by atomic percentage, is: Ni 30-40%, Co 15-20%, Cr 14-25%, Fe 10-15%, Ti<8.0%, Al<8.0%, B<0.2%.
[0022] According to one embodiment of the present invention, the high-entropy alloy comprises, by atomic percentage: Ni 40%, Co 20%, Cr 15%, Fe 15%, Ti 4%, Al 5.9%, and B 0.1%. This composition is the optimal embodiment obtained through extensive experimental screening. The proportions of Ni, Co, and Fe are optimized to achieve the best match in soft magnetic properties, maximizing high-frequency hysteresis loss and natural resonance absorption; Cr is at the median of the preferred range, enabling the formation of the densest and most continuous passivation layer; 5.9% Al and 4% Ti provide auxiliary oxidation resistance and solid solution strengthening without significantly reducing conductivity; and 0.1% B provides effective grain boundary pinning without causing grain boundary embrittlement.
[0023] According to one embodiment of the present invention, the cross-sectional shape of the mesh array is honeycomb, rectangular, circular, or irregular polygonal. By selecting different cross-sectional shapes, the mechanical strength, deformation resistance, and optical diffraction characteristics of the mesh can be further adjusted while ensuring basic shielding effectiveness and light transmittance, so as to adapt to the differentiated needs of different scenarios such as aerospace and optoelectronic detection.
[0024] According to one embodiment of the present invention, the transparent substrate is a sapphire, quartz glass, MgF2, CaF2, ZnS, or ZnSe optical substrate. By selecting different substrate materials, the thermal expansion coefficients of the high-entropy alloy grating and the substrate can be better matched, reducing thermal stress while meeting the optical transmission requirements of specific wavelengths, thus expanding the application scope of the present invention.
[0025] According to one embodiment of the present invention, the linewidth of the grating array is 1-5 μm, and the aperture is 50-100 μm. The grating array, with a linewidth of 1-5 μm and an aperture of 50-100 μm, belongs to a periodic aperture-type metal grating structure: the aperture is much larger than the wavelength of visible light (380-780 nm), but the diffraction effect on visible light is extremely weak, ensuring a visible light transmittance >85%; the linewidth is controlled at the micrometer scale, making the duty cycle and period of the grating adjustable, further optimizing the balance between electromagnetic shielding effectiveness and light transmittance.
[0026] According to one embodiment of the present invention, the linewidth of the mesh array is 2 μm and the aperture is 80 μm. These parameters are preferred values. The 2.0 μm linewidth ensures the mechanical strength and conductive continuity of the mesh lines, while avoiding excessive width that would reduce light transmittance. The 80 μm aperture is much larger than the wavelength of visible light, resulting in extremely weak diffraction effects and ensuring high light transmittance. The synergistic effect of these linewidth and aperture geometric parameters with the properties of the high-entropy alloy material enables the antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh of the present invention to achieve excellent comprehensive performance with a shielding effectiveness >50 dB and a visible light transmittance >85% in the 1-6 GHz frequency band.
[0027] According to one embodiment of the present invention, the thickness of the high-entropy alloy film is 350-700 nm. Controlling the thickness of the high-entropy alloy film to 350-700 nm ensures sufficient conductive layer thickness to maintain low sheet resistance and efficient shielding, while avoiding excessive thickness that could lead to decreased light transmittance or excessive internal stress.
[0028] According to one embodiment of the present invention, the internal grains of the high-entropy alloy film have a columnar crystal morphology and a grain size of 17±1nm.
[0029] The second objective of this invention is to provide a method for preparing an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid.
[0030] To achieve the above-mentioned objectives, the specific technical solution is as follows: A method for preparing an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid includes the following steps: S1 performs a pre-cleaning treatment on the transparent substrate; S2 spin-coats photoresist onto the pretreated substrate surface, and after exposure and development, forms a mask pattern with a periodic grid microstructure array. S3 employs magnetron sputtering, using a pre-proportioned high-entropy alloy target to deposit high-entropy alloy thin films on a substrate and a photoresist mask. S4 immerses the deposited substrate in the photoresist remover to dissolve the photoresist, strips the redundant alloy film layer in the non-grid area, and leaves a high-entropy alloy grid array on the substrate. S5 performs chemical mechanical polishing on the stripped substrate; S6 performs low-temperature annealing on the polished substrate in a vacuum or inert gas atmosphere.
[0031] According to embodiments of the present invention, the principle and beneficial effects of one of the technical solutions are as follows: The cleaning pretreatment in step S1 ensures that the substrate surface is clean and improves the adhesion of subsequent film layers; Step S2 uses photolithography to form a mask pattern, which can precisely control the linewidth (1-5 μm), aperture (50-100 μm) and cross-sectional shape of the grid, to achieve a periodic aperture structure and ensure high light transmittance (>85%). Step S3 employs magnetron sputtering, utilizing a pre-proportioned high-entropy alloy target. The multi-principal element synergistic effect ensures that the deposited film can fully inherit the component ratio of the target, achieving precise control of the composition. The stripping process in step S4 can completely remove the redundant alloy film layer in the non-grid area, avoiding the problems of linewidth widening and sidewall roughness caused by wet etching, and ensuring the edge steepness and dimensional accuracy of the grid lines. The chemical mechanical polishing in step S5 can remove the slight warping of the edges of the grid lines after stripping and the sharp protrusions caused by processing stress, reduce the surface roughness to the sub-nanometer level, eliminate the sharp discharge effect and thermal stress concentration source under high-power microwaves, and delay local temperature rise and thermal oxidation. The low-temperature annealing treatment in step S6 utilizes the hysteresis diffusion effect of high-entropy alloys. The annealing treatment can eliminate the residual stress generated during the deposition process, while inhibiting abnormal grain growth and inducing the formation of high-density nano-polycrystalline or twinned morphologies, thereby further enhancing the mechanical properties and high-temperature stability of the material.
[0032] According to one embodiment of the present invention, in step S3, the substrate temperature for magnetron sputtering is 150-250°C, and the working gas is argon. Maintaining the substrate temperature at 150-250°C improves the adhesion between the thin film and the substrate while preventing excessive temperature from causing photoresist deformation or excessive internal stress in the thin film. Using argon as the working gas prevents the introduction of impurities.
[0033] According to one embodiment of the present invention, in step S5, the chemical mechanical polishing uses a silica polishing slurry with an abrasive particle size of 30-80 nm, a polishing load of 30-70 kPa, and a polishing time of 2-5 min. The silica polishing slurry with an abrasive particle size of 30-80 nm can effectively remove micron-level protrusions without causing excessive wear to the submicron-level grid lines. It should be noted that existing conventional CMP polishing parameters (such as load and time), if directly applied to high-entropy alloy micro / nano grids, may lead to line breakage or excessive wear. The synergistic control of the polishing load of 30-70 kPa and the polishing time of 2-5 min in this invention can remove the sharp edges and warping of the grid lines while maintaining the overall height and cross-sectional shape of the grid, avoiding excessive polishing that could lead to line thinning or breakage. This polishing step eliminates macroscopic stress concentration points caused by processing stress, reducing the surface roughness of the grid to the sub-nanometer level. This effectively suppresses the tip discharge effect and thermal stress concentration under high-power microwave irradiation, delays local temperature rise and thermal oxidation, and significantly improves the thermal shock resistance life of the grid.
[0034] According to one embodiment of the present invention, in step S6, the low-temperature annealing temperature is 400-550°C, and the annealing time is 1-4 hours; the low-temperature annealing is carried out in a vacuum environment with a vacuum degree of 5×10⁻⁶. -4 torr.
[0035] The annealing temperature of 400-550℃ is crucial for the hysteresis diffusion effect of high-entropy alloys to take effect. Below 400℃, residual stress is not fully released, and it is difficult to induce high-density nanocrystals; above 550℃, abnormal grain growth may be induced. Annealing time of 1-4 hours ensures sufficient stress release and full nanocrystal formation. This invention utilizes the hysteresis diffusion effect of high-entropy alloys in low-temperature annealing to maintain the nanocrystalline structure while eliminating internal stress, giving the grid film excellent thermal stability and creep resistance at high temperatures.
[0036] Vacuum annealing protects antioxidant elements such as Cr and Al from premature consumption during the annealing stage, ensuring their uniform distribution within the crystal in a solid solution state. This guarantees that during actual high-temperature service (even in environments up to 1000°C), they can diffuse to the surface in a timely manner to form a continuous and dense self-healing passivation film. Furthermore, the vacuum environment provides an inert thermodynamic background for segmented heating, allowing the heating rate control to truly serve atomic migration regulation rather than being limited by oxidation kinetics.
[0037] According to one embodiment of the present invention, in step S6, the low-temperature annealing temperature is 450-500°C, and the annealing time is 2 hours. This preferred parameter range represents the optimal process window. Annealing at 450-500°C for 2 hours can fully release residual stress from the deposition and processing, while simultaneously utilizing the hysteresis diffusion effect of the high-entropy alloy to suppress abnormal grain growth. The oxidation-resistant, high-temperature-resistant, high-entropy alloy transparent electromagnetic shielding grid obtained under these annealing conditions still exhibits a grain size of approximately 300 nm after heating at 1000°C for 16 hours, without abnormal coarsening.
[0038] According to one embodiment of the present invention, in step S6, the low-temperature annealing employs segmented heating: heating to 200°C at a rate of 0.75 K / sec; heating from 200°C to 450°C at a rate of 0.35 K / sec; and a constant cooling rate of 0.15 K / sec during the low-temperature annealing cooling stage. Segmented heating and cooling are necessary process conditions for achieving optimal pinning effect of element B. Without such precise temperature control, element B will either have insufficient segregation (due to excessively rapid heating) or uneven distribution (due to inappropriate isothermal time). It should be noted that on a scale of 1-5 μm linewidth, it is necessary to eliminate stress, control grain size (10-20 nm), and achieve uniform distribution of grain boundary strengthening phases. This is far more technically challenging than conventional thin film annealing. This application employs precise step-by-step annealing to avoid abnormal growth of columnar crystals during the annealing stage, thereby achieving thermal stability under extreme conditions.
[0039] According to one embodiment of the present invention, the photoresist is a positive photoresist, and the exposure is ultraviolet exposure. By selecting a positive photoresist and ultraviolet exposure, the present invention ensures the dimensional accuracy and repeatability of the grid microstructure array, providing a high-quality mask pattern for subsequent high-entropy alloy thin film deposition and stripping.
[0040] The third objective of this invention is to provide the application of the aforementioned antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh.
[0041] The specific technical solution is as follows: The antioxidant, high-temperature resistant, and high-entropy alloy transparent electromagnetic shielding mesh is used in the fabrication of aerospace cockpit observation windows, optical windows for photoelectric detection equipment, or optical windows for radio frequency front-ends.
[0042] In high-altitude or outer space environments, where temperature changes are drastic and accompanied by prolonged strong electromagnetic radiation, the high-entropy alloy mesh of this invention exhibits hysteresis diffusion and grain boundary strengthening. This allows it to maintain its nanocrystalline structure even under extreme conditions of 300-1000°C and high-frequency electromagnetic waves (MHz-GHz band), without grain coarsening or delamination, ensuring long-term service stability. Simultaneously, the dense oxide passivation layer formed on the surface effectively resists high-temperature oxidation, preventing shielding effectiveness degradation. Compared to traditional pure metal meshes or ITO films, the mesh of this invention has significant advantages in high-temperature resistance, oxidation resistance, and thermal shock resistance, making it particularly suitable for extreme environments such as aerospace and photoelectric detection.
[0043] According to one embodiment of the present invention, after the transparent electromagnetic shielding grid is used to manufacture aerospace cockpit observation windows, optical windows of photoelectric detection equipment, or radio frequency front-end optical windows, the grid grain size remains ≤300nm after working in a high-temperature environment of 100-1000℃ for 0.5-16 hours, and no abnormal grain coarsening or delamination from the substrate occurs. The high-entropy alloy grid material of the present invention, due to its hysteresis diffusion effect and grain boundary pinning mechanism, possesses excellent high-temperature tolerance, meeting the stringent requirements for grid thermal stability under high-power electromagnetic wavelength time or pulse irradiation, thereby ensuring long-term reliable service of the optical window in extreme electromagnetic environments.
[0044] According to one embodiment of the present invention, the transparent electromagnetic shielding grid, when used in the fabrication of observation windows for aerospace cockpits, optical windows for photoelectric detection equipment, or optical windows for radio frequency front-ends, exhibits a shielding effectiveness SE > 50 dB and a visible light transmittance T > 85% under high-power electromagnetic wave irradiation. The shielding effectiveness SE > 50 dB means that it can block the vast majority of incident electromagnetic wave energy, meeting the stringent requirements for electromagnetic shielding in the military and aerospace fields. The visible light transmittance T > 85% ensures the clarity and imaging quality of the optical window. The simultaneous achievement of these two indicators stems from the synergistic effect of the soft magnetic properties (hysteresis loss and natural resonant absorption) of the high-entropy alloy and the periodic aperture grid structure.
[0045] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The invention will now be described in further detail with reference to the figures. Attached Figure Description
[0046] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a flowchart of the preparation method of the antioxidant, high temperature resistant, high entropy alloy transparent electromagnetic shielding grid in Examples 1-3.
[0047] Figure 2The image shows the transmission electron microscope (TEM) characterization of the antioxidant, high-temperature resistant, and high-entropy alloy transparent electromagnetic shielding grid of Example 1 (scale bar 500 nm).
[0048] Figure 3 The image shows a transmission electron microscope (TEM) image (scale bar 200 nm) of the antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh from Example 1 after heat treatment at 1000°C for 64 min; where, Figure 3 (a) is an electron microscope image of the grid before heating. Figure 3 (b) is an electron microscope image of the grid after heating at 1000℃ for 64 min.
[0049] Figure 4 The image shows the transmission electron microscope (TEM) characterization of the antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh of Example 1 after heat treatment at 1000 °C for 64 min (scale bar 500 nm).
[0050] Figure 5 The graph shows the trend of high-temperature resistance characteristics of the antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid of Example 1 after heating in a vacuum muffle furnace and an air atmosphere muffle furnace, respectively. Detailed Implementation
[0051] The terms "preferred," "more preferred," etc., used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.
[0052] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0053] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of the present invention.
[0054] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.
[0055] The high-entropy alloy target used in this invention has a purity of 99.95%.
[0056] The adhesive remover used in this invention is NMP adhesive remover, the main component of which is N-methylpyrrolidone.
[0057] Example 1 An antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid has a transparent substrate and a grid array disposed on the transparent substrate; The aforementioned grid array is composed of a high-entropy alloy thin film, and the composition and content of the high-entropy alloy are shown in Table 1: Table 1. Composition and content of the high-entropy alloy in Example 1
[0058] The thickness of the aforementioned high-entropy alloy film is 500 nm; The linewidth of the aforementioned grid array is 2 μm, and the aperture is 80 μm.
[0059] A method for preparing an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid, the flowchart of which is shown below. Figure 1 As shown, specifically, it includes the following steps: S1 The transparent sapphire substrate was cleaned for 10 minutes in an ultrasonic cleaner containing 99.5% acetone solution and 99.7% anhydrous ethanol solution, respectively. After ultrasonic rinsing with deionized water for 10 minutes, the transparent sapphire substrate was dried to ensure that there was no moisture residue on the surface. S2 spin-coats positive photoresist onto the surface of a transparent sapphire substrate, and after ultraviolet exposure and development, forms a mask pattern with a honeycomb grid microstructure array; S3 employs magnetron sputtering, using pre-mixed high-entropy alloy targets, and sets the vacuum level at 3E. -6 Below torr, high-purity argon gas (99.999%) is introduced to maintain the sputtering pressure and the substrate temperature is maintained at 200 °C, thereby depositing a high-entropy alloy film on the substrate and photoresist mask; S4 immerses the deposited substrate in a 50 °C constant temperature resist solution and lets it stand for 30 min to dissolve the photoresist, peel off the redundant alloy film layer in the non-grid area, and leave a high-entropy alloy grid array on the substrate. The S5 mounts the stripped substrate onto a chemical mechanical polishing (CMP) machine, applies a load of 50 kPa, a main disk rotation speed of 60 rpm, and a silica polishing slurry with an abrasive particle size of 50 nm for 3 minutes of surface polishing. S6 places the polished substrate into a vacuum annealing furnace, setting the vacuum level to 5×10⁻⁶. -4The torr was subjected to stress-relief annealing at 450 ℃ for 2 hours. The annealing process adopted a segmented heating method: heating up to 200 ℃ at a heating rate of 0.75 K / sec; heating up from 200 ℃ to 450 ℃ at a heating rate of 0.35 K / sec; and cooling down at a constant rate of 0.15 K / sec.
[0060] Example 2 The difference between Example 2 and Example 1 is that the contents of Ni, Co and Fe were adjusted in Example 2, and the polishing and annealing parameters were adapted accordingly.
[0061] Specifically: An antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid has a transparent substrate and a grid array disposed on the transparent substrate; The aforementioned grid array is composed of a high-entropy alloy thin film, and the composition and content of the high-entropy alloy are shown in Table 2: Table 2. Composition and content of high-entropy alloy in Example 2
[0062] The thickness of the aforementioned high-entropy alloy film is 500 nm; The linewidth of the aforementioned grid array is 2 μm, and the aperture is 80 μm.
[0063] A method for preparing an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid, the flowchart of which is shown below. Figure 1 As shown, specifically, it includes the following steps: S1 The transparent sapphire substrate was cleaned for 10 minutes in an ultrasonic cleaner containing 99.5% acetone solution and 99.7% anhydrous ethanol solution, respectively. After ultrasonic rinsing with deionized water for 10 minutes, the transparent sapphire substrate was dried to ensure that there was no moisture residue on the surface. S2 spin-coats positive photoresist onto the surface of a transparent sapphire substrate, and after ultraviolet exposure and development, forms a mask pattern with a honeycomb grid microstructure array; S3 employs magnetron sputtering, using pre-mixed high-entropy alloy targets, and sets the vacuum level at 3E. -6 Below torr, high-purity argon gas (99.999%) is introduced to maintain the sputtering pressure and the substrate temperature is maintained at 200 °C, thereby depositing a high-entropy alloy film on the substrate and photoresist mask; S4 immerses the deposited substrate in a 50 °C constant temperature resist solution and lets it stand for 30 min to dissolve the photoresist, peel off the redundant alloy film layer in the non-grid area, and leave a high-entropy alloy grid array on the substrate. The S5 mounts the stripped substrate onto a chemical mechanical polishing (CMP) machine, applies a load of 50 kPa, a main disk rotation speed of 95 rpm, and a silica polishing slurry with an abrasive particle size of 50 nm for 3 minutes of surface polishing. S6 places the polished substrate into a vacuum annealing furnace, setting the vacuum level to 5×10⁻⁶. -4 The torr was subjected to stress-relief annealing at 500 ℃ for 2 hours. The annealing process adopted a segmented heating method: heating up to 200 ℃ at a heating rate of 0.75 K / sec; heating up from 200 ℃ to 450 ℃ at a heating rate of 0.35 K / sec; and cooling down at a constant cooling rate of 0.15 K / sec.
[0064] In Example 2, the Ni content in the target material was increased to near its upper limit, correspondingly diluting the Fe and Co ratios. Excessive Ni-based content led to increased grid hardness and brittleness, making it prone to breakage during peeling and polishing, resulting in a decreased processing yield.
[0065] Example 3 The difference between Example 3 and Example 1 is that the contents of Ni, Co and Fe were adjusted in Example 3, and the polishing and annealing parameters were adapted accordingly.
[0066] Specifically: An antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid has a transparent substrate and a grid array disposed on the transparent substrate; The aforementioned grid array is composed of a high-entropy alloy thin film, and the composition and content of the high-entropy alloy are shown in Table 3. Table 3. Components and content of the high-entropy alloy in Example 3
[0067] The thickness of the aforementioned high-entropy alloy film is 500 nm; The linewidth of the aforementioned grid array is 2 μm, and the aperture is 80 μm.
[0068] A method for preparing an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid, the flowchart of which is shown below. Figure 1 As shown, specifically, it includes the following steps: S1 The transparent sapphire substrate was cleaned for 10 minutes in an ultrasonic cleaner containing 99.5% acetone solution and 99.7% anhydrous ethanol solution, respectively. After ultrasonic rinsing with deionized water for 10 minutes, the transparent sapphire substrate was dried to ensure that there was no moisture residue on the surface. S2 spin-coats positive photoresist onto the surface of a transparent sapphire substrate, and after ultraviolet exposure and development, forms a mask pattern with a honeycomb grid microstructure array; S3 employs magnetron sputtering, using pre-mixed high-entropy alloy targets, and sets the vacuum level at 3E.-6 Below torr, high-purity argon gas (99.999%) is introduced to maintain the sputtering pressure and the substrate temperature is maintained at 200 °C, thereby depositing a high-entropy alloy film on the substrate and photoresist mask; S4 immerses the deposited substrate in a 50 °C constant temperature resist solution and lets it stand for 30 min to dissolve the photoresist, peel off the redundant alloy film layer in the non-grid area, and leave a high-entropy alloy grid array on the substrate. The S5 mounts the stripped substrate onto a chemical mechanical polishing (CMP) machine, applies a load of 30 kPa, a main disk rotation speed of 60 rpm, and a silica polishing slurry with an abrasive particle size of 50 nm for 3 minutes of surface polishing. S6 places the polished substrate into a vacuum annealing furnace, setting the vacuum level to 5×10⁻⁶. -4 The torr was subjected to stress-relief annealing at 450 ℃ for 2 hours. The annealing process adopted a segmented heating method: heating up to 200 ℃ at a heating rate of 0.75 K / sec; heating up from 200 ℃ to 450 ℃ at a heating rate of 0.35 K / sec; and cooling down at a constant rate of 0.15 K / sec.
[0069] In Example 3, the Ni content in the target material was reduced to near the lower limit, and the Fe and Co ratios were correspondingly increased. The decrease in the Ni ratio resulted in a reduction in soft magnetic properties and magnetic loss absorption.
[0070] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the content of Ni and Cr was adjusted in Comparative Example 1.
[0071] Specifically: An antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid has a transparent substrate and a grid array disposed on the transparent substrate; The aforementioned grid array is composed of a high-entropy alloy thin film, and the composition and content of the high-entropy alloy are shown in Table 4: Table 4. Composition and content of the high-entropy alloy in Comparative Example 1
[0072] The thickness of the aforementioned high-entropy alloy film is 500 nm; The linewidth of the aforementioned grid array is 2 μm, and the aperture is 80 μm.
[0073] The low Cr content in Comparative Example 1 prevented the high-entropy alloy target from rapidly forming a sufficiently continuous and dense Cr2O3 oxide passivation film on the grid surface, resulting in increased sheet resistance and deteriorated shielding effectiveness.
[0074] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that the high-entropy alloy of Comparative Example 2 does not contain B in its composition.
[0075] Specifically: An antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid has a transparent substrate and a grid array disposed on the transparent substrate; The aforementioned grid array is composed of a high-entropy alloy thin film, and the composition and content of the high-entropy alloy are shown in Table 5: Table 5. Composition and content of the high-entropy alloy in Comparative Example 2
[0076] The thickness of the aforementioned high-entropy alloy film is 500 nm; The linewidth of the aforementioned grid array is 2 μm, and the aperture is 80 μm.
[0077] The absence of boron in the composition of the high-entropy alloy in Comparative Example 2 prevents the formation of grain boundary boride pinning between the nanocrystals of the high-entropy alloy film. At high temperatures, large-area cracks easily occur at the intersection nodes of the grid lines, making the grid lack high-temperature resistance.
[0078] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not perform step S6 annealing during the preparation of the antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid.
[0079] In Comparative Example 3, the lack of annealing treatment resulted in the inability to effectively release the residual internal stress caused by processing and lattice mismatch within the mesh film. This stress accumulated when high-power microwaves were applied (generating instantaneous Joule heating), causing the film's own stress to be released rapidly. This led to severe delamination (detachment) of the high-entropy alloy mesh from the sapphire substrate, and deteriorated the shielding effectiveness.
[0080] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 does not perform the polishing process in step S5 during the preparation of the antioxidant, high temperature resistant, high entropy alloy transparent electromagnetic shielding grid.
[0081] Comparative Example 4, due to the lack of polishing, did not eliminate the sharp edges of the grid lines and surface protrusions caused by the processing, resulting in thermal stress concentration failure when subjected to high-power microwaves (which generate instantaneous Joule heat).
[0082] Performance testing: The antioxidant, high-temperature resistant, and high-entropy alloy transparent electromagnetic shielding grid prepared in Example 1 was characterized by transmission electron microscopy (scale bar 500 nm), and the results are as follows: Figure 2 As shown. By Figure 2 It can be seen that the internal grains of the grid film in Example 1 exhibit a columnar crystal morphology with a grain size of approximately 17 nm. This structure provides an initial reference for the grain evolution after subsequent high-temperature heating treatment.
[0083] The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh from Example 1 was placed in a vacuum muffle furnace and heated at 1000°C for 64 min. The mesh before and after heating was characterized by transmission electron microscopy (scale bar 200 nm). The results are as follows: Figure 3 As shown, Figure 3 (a) is an electron microscope image of the grid before heating. Figure 3 Image (b) is an electron microscope image of the grid after heating at 1000℃ for 64 min. Figure 3 It can be seen that after heating, the internal grains of the grid film change from columnar crystals (about 17 nm) to equiaxed nanocrystals, with the grain size distributed in the submicron range of 20-280 nm.
[0084] The results show that despite being heated to an extreme high temperature of 1000℃ for 64 min, the grid grains remained in the nanometer to submicron range, without any abnormal coarsening. Therefore, the multi-principal-element solid solution structure of the high-entropy alloy produces a significant hysteresis diffusion effect. The difference in atomic size leads to lattice distortion, which significantly reduces the long-range migration rate of atoms at high temperatures, thereby inhibiting rapid grain growth. Simultaneously, boron (B) elements segregate at grain boundaries to form borides, exerting a grain boundary pinning effect, further hindering grain boundary slip and migration. The combined effect of these two mechanisms enables the grid to effectively resist Joule heating induced by high-power electromagnetic waves, solving the technical problem of plastic deformation, fracture, and even melting of existing pure metal grids under high-power irradiation due to grain coarsening.
[0085] In addition, high-density nanograin boundaries are beneficial for enhancing electron scattering and increasing resistivity, thereby significantly reducing eddy current losses under high-frequency alternating electromagnetic fields, indirectly improving shielding effectiveness and reducing Joule heating.
[0086] The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh from Example 1 was placed in a vacuum muffle furnace and heated at 1000 °C for 64 min. The mesh after heating at 1000 °C was characterized by transmission electron microscopy (TEM) with a scale bar of 500 nm. The characterization results are as follows: Figure 4 As shown in the figure, under high-temperature heating conditions, elemental agglomeration and segregation occur within the high-entropy alloy. Elements such as Al, Cr, and Ti diffuse to the film surface, forming a dense and stable composite passivating oxide film that hinders further diffusion of oxygen atoms into the mesh film, thus enhancing its oxidation resistance. Furthermore, element B, by forming grain boundary borides, pins the grain boundary slip of nanocrystals, inhibiting high-temperature thermal deformation. This self-healing oxidation resistance mechanism solves the technical problem of existing pure metal meshes (such as Cu and Ag) which, due to the formation of loose oxides, cannot prevent continuous internal oxidation, leading to a sharp increase in resistance and a decrease in shielding effectiveness.
[0087] The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh from Example 1 was placed in a vacuum muffle furnace and an air muffle furnace for heating, respectively. The trend graphs of its high-temperature resistance characteristics were obtained. The vacuum muffle furnace was heated at 1000°C for 16 hours, and the air muffle furnace was heated at 1000°C for 32 minutes. The test results are as follows: Figure 5 .from Figure 5 It can be seen that in an air muffle furnace, after heating at 1000℃ for 16 minutes, the grain size inside the anti-oxidation, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh film increased to about 250 nm. After 32 minutes, recrystallization occurred, causing the grain size to decrease to about 220 nm. In a vacuum muffle furnace, after heating at 1000℃ for 1 hour, the grain size increased to about 270 nm, and after heating for 16 hours, the grain size reached about 300 nm.
[0088] The results show that, regardless of whether in a vacuum or air environment, the grain size of the grating remains below 300 nm after heating at 1000 °C. Specifically, after 16 hours of heating at 1000 °C in a vacuum environment, the grain size only increased from approximately 17 nm to approximately 300 nm, far from reaching micrometer-level abnormal coarsening. This contrasts sharply with the rapid coarsening of pure metal grains to several micrometers or even tens of micrometers under the same conditions. These data further demonstrate that high-entropy alloy grating materials, due to their hysteresis diffusion effect and grain boundary pinning mechanism, possess excellent high-temperature tolerance limits, meeting the stringent requirements for grating thermal stability under high-power electromagnetic wavelength time or pulse irradiation, thus ensuring the long-term reliable service of optical windows in extreme electromagnetic environments.
[0089] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0090] The above embodiments are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the appended claims.
[0091] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. An antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid, characterized in that: Includes a transparent substrate and a grid array disposed on the transparent substrate; The grid array is composed of a high-entropy alloy thin film, the high-entropy alloy comprising Fe, Co, Ni, Cr, and B, with a Cr content of 14-25 at.% and a B content of 0.05-0.2 at.%. The high-entropy alloy film has columnar crystal morphology inside, and the average width of the grains is 10-20 nm.
2. The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid according to claim 1, characterized in that: In the high-entropy alloy, the Ni content is 30-55 at.%, the Co content is 12-26 at.%, the Cr content is 14-25 at.%, and the Fe content is 8-20 at.%.
3. The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid according to claim 1, characterized in that: The high-entropy alloy also includes at least one of Al, Ti, V, Nb, Mo, W, Ta, Zr, and Mn.
4. The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid according to claim 3, characterized in that: The high-entropy alloy comprises Al and Ti, with Al content <8.0 at.% and Ti content <8.0 at.%.
5. The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh according to any one of claims 1 to 4, characterized in that: The linewidth of the grid array is 1-5 μm, and the aperture is 50-100 μm.
6. The antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding mesh according to any one of claims 1 to 4, characterized in that: The thickness of the high-entropy alloy film is 350-700 nm.
7. A method for preparing an antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid as described in any one of claims 1 to 6, characterized in that: Includes the following steps: S1 performs a pre-cleaning treatment on the transparent substrate; S2 spin-coats photoresist onto the pretreated substrate surface, and after exposure and development, forms a mask pattern with a periodic grid microstructure array. S3 employs magnetron sputtering, using a pre-proportioned high-entropy alloy target to deposit high-entropy alloy thin films on a substrate and a photoresist mask. S4 immerses the deposited substrate in the photoresist remover to dissolve the photoresist, strips the redundant alloy film layer in the non-grid area, and leaves a high-entropy alloy grid array on the substrate. S5 performs chemical mechanical polishing on the stripped substrate; S6 performs low-temperature annealing on the polished substrate in a vacuum or inert gas atmosphere.
8. The method for preparing the antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid according to claim 7, characterized in that: In step S6, the low-temperature annealing temperature is 400-550℃, and the annealing time is 1-4 hours; the low-temperature annealing is carried out in a vacuum environment with a vacuum degree of 5×10⁻⁶. -4 torr.
9. The method for preparing the antioxidant, high-temperature resistant, high-entropy alloy transparent electromagnetic shielding grid according to claim 8, characterized in that: In step S6, the low-temperature annealing adopts a segmented heating method, heating to 200℃ at a heating rate of 0.75K / sec; from 200℃ to 450℃ at a heating rate of 0.35K / sec; and the low-temperature annealing cooling stage has a constant cooling rate of 0.15K / sec.